Potential Words in Indonesian Language: : A Study of Generative Morphology - Sirulhaq, Ahmad; Sukri, Sukri; Jafar, Syamsinas; Burhanuddin, Burhanuddin (Bina Nusantara University, 2022)
The research aimed to identify potential words in the Indonesian language and sought to explain why these words were not included in Indonesian vocabulary lists or were difficult to realize in natural conversations. In order to achieve these goals, data were collected using introspection, documentation, and interview methods. Furthermore, the collected data were analyzed using a generative morphology approach, mainly related to concepts of potential words. According to the approach, each language has (1) a List of Morphemes (LM), (2) Word Formation Rules (WFR), and (3) a Filter (F). WFR stated that every language was capable of producing new potential words, yet not all those potential words could easily pass through the filter to enter the lexicon of actual words used in real life. The potential words discussed in the research were restricted to those showing morpho-syntactic interconnection among Indonesian affixes. The results indicate that numerous potential words in the Indonesian language are constructed out of such affixal interconnection. However, the potential words do not surface in the lexicon for two reasons: first, because the words fail to compete with others that compensate for their absence; second, because the words are difficult to manifest due to their low frequency in everyday speech.